Inflation, human capital and Tobin's q - Parantap Basu; Max Gillman; Joseph Pearlman (Cardiff University, Cardiff Business School, 2009)
A pervasive empirical finding for the US economy is that inflation is negatively correlated with the normalized market price of capital (Tobin's q) and growth. A dynamic stochastic general equilibrium model of endogenous growth is developed to explain these stylized facts. In this model, human capital is the principal driver of self-sustained growth. Long run comparative statics analysis suggests that inflation diverts scarce time resource to leisure which lowers human capital utilization. This impacts growth adversely and modulates capital adjustment cost downward resulting in a decline in Tobin's q. For the short run, a Tobin effect of inflation on growth weakens the negative association between inflation and q.
Keywords: 330; Inflationsrate; Wirtschaftswachstum; Tobin's Q; USA; Theorie